2006
DOI: 10.1002/imhj.20081
|View full text |Cite
|
Sign up to set email alerts
|

A prevention and promotion intervention program in the field of mother–infant relationship

Abstract: The purpose of the study was to analyze the efficacy of early home-visiting intervention in enhancing the quality of mother-infant interaction in psychosocial risk and depressive risk motherinfant dyads. Thirty depressive risk, 28 psychosocial risk, and 33 low-depressed and low-risk mothers were randomly distributed between the Home Visiting Program and control groups. Attachment ͑Adult Attachment Interview; Main & Goldwyn, 1997͒ and maternal representations during pregnancy ͑Inter-view of Maternal Representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 37 publications
3
46
1
8
Order By: Relevance
“…À la lumière de ces études, on comprend que plusieurs chercheurs aient développé des programmes d'intervention en vue d'améliorer les interactions mère-enfant à titre de levier pour promouvoir le développement des enfants (Ammaniti et al, 2006 ;Tarabulsy et al, 2008).…”
Section: Lien Entre La Sensibilité Maternelle Et Le Développement De unclassified
“…À la lumière de ces études, on comprend que plusieurs chercheurs aient développé des programmes d'intervention en vue d'améliorer les interactions mère-enfant à titre de levier pour promouvoir le développement des enfants (Ammaniti et al, 2006 ;Tarabulsy et al, 2008).…”
Section: Lien Entre La Sensibilité Maternelle Et Le Développement De unclassified
“…In total, 30 studies were identified, 175,178,[180][181][182][183][184]188,189,191,[194][195][196]198,[200][201][202][203][205][206][207][208]211,212,218 29 of which were delivering an intervention in a hypothesised 'at-risk' group to improve attachment security 129,[175][176][177][178][180][181][182][183][184][185][186]189,191,[194][195][196]198,[200][201][202][203]205,206,208,211,…”
Section: Main Systematic Reviewmentioning
confidence: 99%
“…188 The studies were published between 1985 and 2012 and were undertaken in a variety of countries: five in the UK, 176,188,189,207,208 14 in the USA, 177,[180][181][182][184][185][186]191,194,196,200,201,205,211 three in the Netherlands, 178,198,203 three in Canada, 175,195,218 one in Germany, 202 one in Australia, 130 one in Italy, 206 one in Finland 212 and one in Lithuania. 183 l Eight studies were identified in the main systematic review that evaluated the intervention using a measure that assessed a disorganised pattern.…”
Section: Main Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A second important premise underlying program intervention focuses on the therapeutic aspect of didactic relationship that is developed in-home visitation. Numerous researchers point that the relationship between the home visitor and the mother serves as a "parallel process" to help the mother interact better with her infant (Ammaniti, et al 2006;Lyons-Ruth, et al 1990;Olds, et al 1997;Sadler, Slade, & Mayers, 2006;Stern, 2006;Zeanah, et al 2006).…”
Section: Introductionmentioning
confidence: 99%